1998
DOI: 10.1139/w98-005
|View full text |Cite
|
Sign up to set email alerts
|

Emulsification of crude oil by an alkane-oxidizingRhodococcusspecies isolated from seawater

Abstract: A Rhodococcus species, the best of 99 oil-emulsifying bacteria isolated from globally distributed seawater samples, was characterized. The bacterium produced very stable oil-in-water emulsions from different crude oils with various contents of aliphatic and aromatic compounds by utilizing the C11 to C33 n-alkanes as carbon and energy sources. The presence of alkanes induced the formation of a hydrophobic cell surface that permitted oil-associated exponential growth and where an extensive emulsification of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…The polymers can be expressed on the cell surface and so react with the organic phase and disperse it (Bredholt et al, 1998). It has been reported that some intact and washed bacteria can stabilize oil/water emulsions by adhering to the oil-water interface; these bacteria hinder the coalescence of oil droplets and interact to form emulsion gels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymers can be expressed on the cell surface and so react with the organic phase and disperse it (Bredholt et al, 1998). It has been reported that some intact and washed bacteria can stabilize oil/water emulsions by adhering to the oil-water interface; these bacteria hinder the coalescence of oil droplets and interact to form emulsion gels.…”
Section: Discussionmentioning
confidence: 99%
“…In biphasic systems, emulsification is not always just the result of the activity of biosurfactants; certain intact bacterial cells are also able to stabilize oil/water emulsions without changing the interfacial tension, by inhibition of droplet coalescence (Bredholt et al, 1998;Dorobantu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For screening of bacterial growth on organosulfur compounds, emulsion agar containing 1% (vol/vol) dodecane was prepared as described previously (2). The sulfur concentration in the oil was 25 mM.…”
Section: Methodsmentioning
confidence: 99%
“…It enhances the bioavailability of the oil and thus increases the biodegradation rate (Bredholt et al, 1998;Minf et al, 2011;Hassanshahian et al, 2012). Very often the growth of microorganisms on hydrocarbons is accompanied by the emulsification of the hydrocarbon in the medium, and in most cases this has been attributed to the production of surface-active compounds (Desai and Banat,1997).…”
Section: Issn: 2320-5407mentioning
confidence: 99%